Pelatihan Menulis Paragraf Sederhana Bagi kelas X Jurusan Teknik Komputer dan Jaringan SMK Swasta Yapim Biru-Biru - Kartina Rahmadhani Rambe; Bambang Nur Alamsyah Lubis; Jusnizar Sinaga; Saut Mardame Simamora; Sri Ramadhani (Journal Of Human And Education (JAHE), 2023)
Simple paragraph writing training for tenth grade student Teknik Komputer Jaringan program at SMKSwasta Yapim Biru-Biru was a training that aimed to broaden students’ knowledge in simple paragraph writing in English which could be applied in classroom learning activity at English subject. The subject of the training was 40 tenth grade students of Teknik Komputer dan Jaringna program at SMK Swasta Yapim Biru-Biru. Lecture and discussion was used as the method of training which provided the information of simple paragraph writing that was able to apply in classroom activity, later on, students were able to write full text optimally, and followed by discussion session which aim to provide opportunities to ask question about simple paragraph. The results of this training reflect that there was more information and that students' abilities in writing simple paragraphs have gotten stronger, as seen due to the outcomes of writing simple paragraphs of students who followed the guidelines for writing a paragraph (outline of paragraph).